2016
DOI: 10.3390/pharmaceutics8030027
|View full text |Cite
|
Sign up to set email alerts
|

Tolterodine Tartrate Proniosomal Gel Transdermal Delivery for Overactive Bladder

Abstract: The goal of this study was to formulate and evaluate side effects of transdermal delivery of proniosomal gel compared to oral tolterodine tartrate (TT) for the treatment of overactive bladder (OAB). Proniosomal gels are surfactants, lipids and soy lecithin, prepared by coacervation phase separation. Formulations were analyzed for drug entrapment efficiency (EE), vesicle size, surface morphology, attenuated total reflectance Fourier transform infrared (ATR-FTIR) spectroscopy, in vitro skin permeation, and in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 37 publications
0
29
0
Order By: Relevance
“…Anti-hypersensitive drug lacidipine loaded transdermal proniosomes were produced by using cremophor RH as nonionic surfactant (Soliman et al, 2016). Rajabalaya et al (2016) successfully encapsulated oxybutynin chloride in proniosomes for its transdermal delivery in overactive bladder therapy. It was obvious from the results that proniosomes provide high drug permeation and entrapment efficiency; improve therapeutic efficacy and rapid salivary secretion recovery (Rajabalaya et al, 2016).…”
Section: Dermal and Transdermal Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…Anti-hypersensitive drug lacidipine loaded transdermal proniosomes were produced by using cremophor RH as nonionic surfactant (Soliman et al, 2016). Rajabalaya et al (2016) successfully encapsulated oxybutynin chloride in proniosomes for its transdermal delivery in overactive bladder therapy. It was obvious from the results that proniosomes provide high drug permeation and entrapment efficiency; improve therapeutic efficacy and rapid salivary secretion recovery (Rajabalaya et al, 2016).…”
Section: Dermal and Transdermal Deliverymentioning
confidence: 99%
“…Rajabalaya et al (2016) successfully encapsulated oxybutynin chloride in proniosomes for its transdermal delivery in overactive bladder therapy. It was obvious from the results that proniosomes provide high drug permeation and entrapment efficiency; improve therapeutic efficacy and rapid salivary secretion recovery (Rajabalaya et al, 2016). Similarly, transdermal proniosomes were designed incorporating tolterodine tartrate (TT) for the management of overactive bladder (OAB).…”
Section: Dermal and Transdermal Deliverymentioning
confidence: 99%
“…Elshafeey et al developed controlled release of the drug into the systemic circulation with the use of TT microemulsion, which was advantageous in prevention of nocturnal enuresis with improvement in patient compliance (16). Similar studies of both oxybutynin and TT proniosomal gel were reported by our group to be suitable for transdermal route, which reduced the dry mouth eff ect compared to the oral route in our earlier studies (17,18). The drug had not been explored for transdermal delivery as a patch and this is the fi rst study that analyses the effi cacy of this formulation.…”
mentioning
confidence: 55%
“…Optimised PNG (1 g) was dissolved in 20 mL of DW and the electrode was then dipped into gel formulation and constant reading was noted. The measurements of pH of formulation were replicated three times 24 .…”
Section: Determination Of Phmentioning
confidence: 99%
“…In vitro release studies of optimised PNG formulation was performed by Franz diffusion cell (Make: Orchid Scientifics Model: FDC03) using cellophane membrane previously soaked in phosphate buffer pH 5.5 24 for 24 h. The cellophane membrane (Make: Pal life sciences ltd. pore size=0.45µm) was mounted between the donor and receptor compartment both containing phosphate buffer pH 5.5. Weighed quantity of optimised PNG (0.3 g containing 4.4 mg of drug) was applied on donor side of the cellophane membrane.…”
Section: Determination Of Drug Contentmentioning
confidence: 99%